A study on the students’ speaking problems faced in the national university debating championship (NUDC) selection at universitas PGRI Wiranegara - Khusnia, Irma; Othman, Norziah (Journal of English Language Proficiency, 2025)
Speaking involves conveying ideas verbally using language, but many students struggle with it, especially in public settings. This study explores the speaking challenges students face during debates and their strategies for overcoming these issues. Focusing on the 2022 National University Debating Championship (NUDC) selection at Universitas PGRI Wiranegara, the research aims to identify the speaking problems encountered by students and how they addressed them. Employing a qualitative descriptive method, the study involved 16 students from English Study Program department. Data was gathered through questionnaires and interviews conducted from May 20 to 25, 2024. The results showed that students struggled with limited vocabulary, bad grammar, and fear of mispronunciation. Additionally, many experienced anxiety about making mistakes and felt nervous when speaking English or in public. The study also identified several strategies students used to manage these problems: using similar word, practice, staying calm, learning about the topic, staying on topic, focusing, repeating key points, and maintaining confidence. In conclusion, students faced various speaking challenges but developed effective strategies to handle them during the NUDC selection. The researcher recommends that future studies broaden the scope to include a wider range of participants across Indonesia.